2005
DOI: 10.2106/jbjs.d.02011
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Extremity Phocomelia Reexamined

Abstract: We propose that cases previously classified as upper-extremity phocomelia represent a spectrum of severe longitudinal dysplasia, as none of the sixty extremities that we studied demonstrated a true intercalary deficiency. These findings have both developmental and genetic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Finally, we will present new information regarding the underlying etiology of the various conditions and propose a modification to the IFSSH classification that is based on current concepts of developmental biology. 40,41 .…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we will present new information regarding the underlying etiology of the various conditions and propose a modification to the IFSSH classification that is based on current concepts of developmental biology. 40,41 .…”
Section: Historymentioning
confidence: 99%
“…The classification was expanded by James et al 50 in 1999 to recognize radial-sided deficiencies limited to the carpus (type 0) and thumb (type N). More recently, the classification was extended by Goldfarb et al 40 to include type V. Type N. The radius and carpus are normal, with deficiencies limited to the thumb (see hypoplastic-thumb classification above).…”
Section: Deficiencies Of the Radiusmentioning
confidence: 99%
See 2 more Smart Citations
“…We couldn't classify our cases according to the Frantz and O'Rahilly system. We found that the classifications suggested by Tytherleigh-Strong and Hooper (2003) and Goldfarb et al (2005) could be promising alternatives for classification. One upper extremity was classified as type A, one as type B, and 7 as type C by Tytherleigh-Strong and Hooper's system.…”
mentioning
confidence: 96%